The Making of an African Working Class : Politics, Law, and Cultural Protest in the Manual Workers Union of Botswana - Werbner, Pnina (Anthropology, culture, and society., 2014)
Exploration of the formation of a distinctive working class identity among low-paid manual workers in Botswana.